Analysis of harmonic characteristics based on improved double-LCC compensation network structure - Shuyao Sun; Zhizhen Liu; Yanjin Hou; Xianglin Li; Yuxin Xie; Huiqiang Zhai; Xiaozhao Wei (Energy Reports, 2022)
The article firstly analyzes the filtering characteristics of double-LCC circuit in wireless power transfer (WPT) system. By defining voltage interference ratio (VIR), the harmonic interference introduced by inverter output voltage square waveform is represented. The ability of suppressing harmonic voltage source interference with different frequency of each branch of compensation network is obtained by analyzing VIR. In order to further reduce the harmonic content of each branch of circuit and decrease the harmonic introduction from the input-side, the article adopts an LC-double-LCC topology circuit. That is, an LC resonant part is connected in series at the input-side of circuit. The VIR of both double-LCC and new structure are compared by building mathematical model, and it is proved that the new structure has better ability to restrain interference. The total harmonic distortion (THD) of input-side current is calculated and the relation between the values of LC part, coupling coefficient, load and THD is quantitatively expressed. The sensitivity analysis in detuning condition of two structures is conducted. When the frequency offset becomes larger, the new topology shows better effect on inhibiting the increase of capacitive and inductive degree of the input impedance angle. The efficiency of WPT system with LC-double-LCC structure is analyzed, and reactive power of input-side is expressed by the value of LC part. With the parameters selected in this article, the input reactive power decreases 55.6% and power factor increases 0.68% after adding LC part. The results of simulation and calculation show that the LC-double-LCC structure has higher efficiency and larger power factor. An experimental platform is built and the theoretical results are verified.